Probabilistic quantitative precipitation forecasting using Ensemble Model Output Statistics - Scheuerer, Michael (Quarterly journal of the Royal Meteorological Society, 2014)
Statistical post-processing of dynamical forecast ensembles is an essential component of weather forecasting. In this article, we present a post-processing method which generates full predictive probability distributions for precipitation accumulations based on ensemble model output statistics (EMOS). We model precipitation amounts by a generalized extreme value distribution which is left-censored at zero.